In-field 3D printing of form-fitted generatively designed components—a case study on paralympic sit-ski equipment - Nesheim, O. S.; Eikevåg, S. W.; Steinert, M.; Elverum, C: W. (Frontiers in Mechanical Engineering, 2024)
Creating specialized components featuring complex structures typically involves extensive time, CAD modelling and manual labor. However, with the right combination of tools and knowledge, complex components can be generated, manufactured, and utilized within hours, rather than weeks or months. By creating a portable manufacturing setup, the designer can produce components on site, significantly enhancing accessibility. An example where time and accessibility are of vital importance is in paralympic cross country skiing where training schedules are tight and snow conditions vary. The aim of this study was to generate and manufacture form-fitted, lightweight knee-supports for a Paralympic sit-ski athlete within 4 days. This was done by 3D printing components generated using Fusion 360s Generative Design (GD), based on inputs from the athlete`s geometry, material testing and force data resulting from the athlete`s weight and movement. A precise fit around the knees was achieved using a high-accuracy 3D scanner and modelling software to create an adjustable prototype to determine knee positions and key angles. Force data from the knees were gathered using a digital twin sit-ski. Based on the collected data, the maximum forces inserted into the GD model were 700N and 500N for the right and left knee, respectively. Material data was obtained through testing ABS samples manufactured under the same conditions as the knee-supports themselves. The Young`s modulus was calculated to EXY=1.945±0.061GPa and EXZ=2.123±0.108GPa and UTS was sXY=31.408±0.774MPa and sXZ=25.859±1.956MPa. The GD model generated seven models to choose from for each knee. The supports were manufactured using a 3D printer modified to increase the volumetric flow, effectively reducing manufacturing time. Manufacturing time of the final knee-supports were 6 h 33 min and 7 h 24 min and the total weight of the components including support structures were 468 g and 532 g for the right and left knee, respectively. Later optimized print settings reduced the manufacturing time to 4 h 40 min. In total, two iterations of knee-supports were produced, and the final lightweight versions were mounted onto the sit-ski within 4 days. Qualitative feedback from the athlete revealed improved fit, increased stability, surprisingly short manufacturing time and a generally pleasing result.